Digital holographic image and video projection system - Ramos, Micael Aléxis Pinto Hilário (2023)
This document presents the work developed in the creation of a holographic system for real-time image and video projection. The main motivation behind this project lies in its complexity, addressing both the generation of holographic videos from 2D images (or image sequences) and their reconstruction and projection in an experimental setup. The initial phase of this work involved researching the basic concepts of holography, followed by the study of various computational holography algorithms. These efforts culminated in a system capable of real-time holographic projection using a spatial light modulator. Despite its functionality, the created system has some limitations for more complex videos and economic feasibility due to the high cost of a spatial light modulator. Therefore, suggestions for future work to enhance the system and overcome these limitations are proposed, concluding this document.